Antioxidant Capacity and Total Phenolic Content in Fruit Tissues from Accessions of Capsicum chinense Jacq. (Habanero Pepper) at Different Stages of Ripening - Lizbeth A. Castro-Concha; Jemina Tuyub-Che; Angel Moo-Mukul; Felipe A. Vazquez-Flota; Maria L. Miranda-Ham (The Scientific World Journal)
In the past few years, there has been a renewed interest in studying a wide variety of food products that show beneficial effects on human health. Capsicum is an important agricultural crop, not only because its economic importance, but also for the nutritional values of its pods, mainly due to the fact that they are an excellent source of antioxidant compounds, and also of specific constituents such as the pungent capsaicinoids localized in the placental tissue. This current study was designed to evaluate the antioxidant capacity and total phenolic contents from fruits tissues of two Capsicum chinense accessions, namely, Chak k’an-iik (orange) and MR8H (red), at contrasting maturation stages. Results showed that red immature placental tissue, with a Trolox equivalent antioxidant capacity (TEAC) value of 55.59 μmols TE g−1 FW, exhibited the strongest total antioxidant capacity using both the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and the CUPRAC methods. Placental tissue also had the highest total phenolic content (27 g GAE 100 g−1 FW). The antioxidant capacity of Capsicum was directly related to the total amount of phenolic compounds detected. In particular, placentas had high levels of capsaicinoids, which might be the principal responsible for their strong antioxidant activities.